Investigating the Role of Foreign Direct Investment on Youth Unemployment Rate in Indonesia - Olivia Tanaya; Suyanto Suyanto (Binus Business Review, 2023)
Youth unemployment is a contemporary socioeconomic problem in many countries. Although it is a negative phenomenon, this number can be translated into different perspectives as it offers plenty of available job force not only in terms of age and easily adaptable workers but also opportunities for low-wage workers. Unfortunately, despite having a high Foreign Direct Investment (FDI) and economic growth rate, Indonesia still suffers from the youth unemployment problem. The research observed a relationship between youth unemployment and FDI in the case of Indonesia from 1991 until 2019. Because of a different situation faced by female and male workers, the research also extended the impact of FDI into gender-specific effects. Data were from World Development Indicator (WDI) in 1991-2019. The short- and long-run situations were analyzed using the Auto-Regressive-Distribution-Lag (ARDL) technique. Based on the findings, it is found that in the short run, FDI can increase youth unemployment in Indonesia. This situation can be due to the reallocation industry, which requires workers’ adjustment. However, in the long run, FDI significantly reduces youth unemployment. Therefore, it concludes that FDI in Indonesia can provide employment opportunities for young people. Next, FDI is found to have a negative and significant effect on female youth unemployment. Meanwhile, there is no significant effect found in male youth unemployment.